Cultivation of oyster mushroom (Pleurotus ostreatus (Jacq.) P. Kumm.) using coffee waste and pulp to mitigate caffeine and pulp related pollution - Calderon Lopez, Juan Carlos; Bhaktikul, Kampanad (Bangladesh Journal of Botany, 2018)
This paper aims to assess the technical, economic, and financial viability of cultivation of mushroom from coffee waste and pulp. The raw material characteristics and technical aspects were analyzed. In techno economic analysis, the investment is defined, and the financing of the project were explained. It is believed that production of mushroom from coffee waste and pulp is feasible as well as profitable in San Salvador. Use of coffee waste in the production of mushroom will prevent its damping in landfills and thus be friendly to environment as well.